Synthesis of exo‐Enamides from Protected Lactams Using a Modified Julia Olefination Reaction: Application to the Synthesis of Spiroaminal Fragments. Issue 29 (1st September 2014) - Gigant, Nicolas; Habib, Samuel; Medoc, Marie; Goekjian, Peter G.; Gueyrard, David; Gillaizeau, Isabelle
Abstract: A modified Julia olefination (Julia–Kocienski) reaction involving lactams has been developed, which gives the corresponding substituted exo ‐enamides in moderate to good yields. An application of this versatile transformation in the synthesis of spiroaminal fragments is also demonstrated. Abstract : A modified Julia olefination (Julia–Kocienski) reaction involving lactams has been developed, which gives the corresponding exo ‐enamides in moderate to good yields. An application of this unprecedented transformation in the synthesis of spiroaminal fragments is also demonstrated.